The heterogeneity of NOTCH1 to tumor immune infiltration in pan-cancer - XiaoJun Duan; Rihan Wu; Mingyang Zhang; Kexin Li; Lei Yu; Huirong Sun; Xingxia Hao; Changshan Wang (Scientific Reports)
Abstract NOTCH1 signaling, a vital regulator of cell proliferation and differentiation, is widely involved in the occurrence and development of malignant tumors. Pharmacological regulation of NOTCH1 is promising in tumor immunotherapy, whereas the effective rate of existing therapies remains low. NOTCH1 functions, as a cancer suppressor or a cancer promoter in different cancers, is engaged in the crosstalk between the immune microenvironment and cancer cells, posing a major challenge to immunotherapy. Therefore, a comprehensive view of the overall situation of NOTCH1-associated immune infiltration in pan-cancer should be built. The relation between NOTCH1 and immune infiltration was initially investigated in this paper. In this study, the data originated from the Genotype-Tissue Expression (GTEx) and the Cancer Genome Atlas (TCGA) databases were input into multiple online bioinformatic tools to study the characteristics of NOTCH1 in pan-cancer. We found that there was obvious heterogeneity in the NOTCH1-associated tumor immune infiltration in pan-cancer. In accordance with the heterogeneity, pan-cancer mainly fell into two categories, i.e., cancers that NOTCH1 promoted immune infiltration (termed hot tumors) and NOTCH1 inhibited immune infiltration (termed cold tumors). We further analyzed the changes of immune infiltration in pan-carcinoma species from the perspectives of NOTCH1 expression, mutation, gene function, tumor metastasis and drugs. NOTCH1 expression was significantly up-regulated in cold tumors but down-regulated in hot tumors. The Gene ontology (GO) enrichment analysis of NOTCH1 with the two categories placed stress on angiogenesis and protein dealkylation, respectively. Further, the gene sets of angiogenesis facilitated immune infiltration, whereas the gene sets of protein dealkylation hindered immune infiltration. The tsRNA associated with NOTCH1 is a type of angiogenin that potentially exerts a significant influence on angiogenesis. We have conducted a meticulous analysis of the function of this tsRNA. NOTCH1 was conducive to cancer-associated fibroblasts (CAFs) immune infiltration, while the metastatic process was more dependent on the differentiation and angiogenesis function of NOTCH1. Accordingly, the heterogeneity of NOTCH1 in immune infiltration was extensively analyzed in this study based on the pan-cancer study, which can contribute to the formulation of specific immunotherapy strategies.